The sum of

Geometry Level 4

S = n = 1 ( 2 sin 4 π 2 n 6 cos 2 π 2 n sin 2 π 2 n ) \displaystyle{\mathcal{S} = \sum_{n=1}^{\infty} \left ( 2 \sin^4 \frac{\pi}{2^n} - 6 \cos^2 \frac{\pi}{2^n} \sin^2 \frac{\pi}{2^n} \right )}


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Atomsky Jahid
Jun 28, 2018

We're going to use the identity sin ( 2 x ) = 2 sin ( x ) cos ( x ) \sin(2x) = 2 \sin(x) \cos(x) and telescoping.

Defining a n a_n to be a n = ( 2 sin 4 π 2 n 6 cos 2 π 2 n sin 2 π 2 n ) = ( 2 sin 2 π 2 n ( sin 2 π 2 n 3 cos 2 π 2 n ) ) = ( 2 sin 2 π 2 n ( 1 4 cos 2 π 2 n ) ) = ( 2 sin 2 π 2 n 8 cos 2 π 2 n sin 2 π 2 n ) = ( 8 cos 2 π 2 n + 1 sin 2 π 2 n + 1 8 cos 2 π 2 n sin 2 π 2 n ) \begin{aligned} a_{n} &= \left( 2 \sin^4 \frac{\pi}{2^n} - 6 \cos^2 \frac{\pi}{2^n} \sin^2 \frac{\pi}{2^n} \right) \\ &= \left( 2 \sin^2 \frac{\pi}{2^n} \left( \sin^2 \frac{\pi}{2^n} - 3 \cos^2 \frac{\pi}{2^n} \right) \right) \\ &= \left( 2 \sin^2 \frac{\pi}{2^n} \left( 1 - 4 \cos^2 \frac{\pi}{2^n} \right) \right) \\ &= \left( 2 \sin^2 \frac{\pi}{2^n} - 8 \cos^2 \frac{\pi}{2^n} \sin^2 \frac{\pi}{2^n} \right) \\ &= \left( 8 \cos^2 \frac{\pi}{2^{n+1}} \sin^2 \frac{\pi}{2^{n+1}} - 8 \cos^2 \frac{\pi}{2^n} \sin^2 \frac{\pi}{2^n} \right) \end{aligned}

Therefore, the summation up to k t h k^{th} term will be S k = n = 1 k ( 8 cos 2 π 2 n + 1 sin 2 π 2 n + 1 8 cos 2 π 2 n sin 2 π 2 n ) = n = 2 k + 1 ( 8 cos 2 π 2 n sin 2 π 2 n ) n = 1 k ( 8 cos 2 π 2 n sin 2 π 2 n ) = 8 cos 2 π 2 k + 1 sin 2 π 2 k + 1 8 cos 2 π 2 sin 2 π 2 \begin{aligned} S_k &= \sum_{n=1}^{k} \left( 8 \cos^2 \frac{\pi}{2^{n+1}} \sin^2 \frac{\pi}{2^{n+1}} - 8 \cos^2 \frac{\pi}{2^n} \sin^2 \frac{\pi}{2^n} \right) \\ &= \sum_{n=2}^{k+1} \left( 8 \cos^2 \frac{\pi}{2^n} \sin^2 \frac{\pi}{2^n} \right) - \sum_{n=1}^{k} \left( 8 \cos^2 \frac{\pi}{2^n} \sin^2 \frac{\pi}{2^n} \right) \\ &= 8 \cos^2 \frac{\pi}{2^{k+1}} \sin^2 \frac{\pi}{2^{k+1}} - 8 \cos^2 \frac{\pi}{2} \sin^2 \frac{\pi}{2} \end{aligned}

As cos π 2 = 0 \cos \frac{\pi}{2} = 0 and lim k sin 2 π 2 k + 1 = 0 \lim_{k\to\infty} \sin^2 \frac{\pi}{2^{k+1}} = 0 , we can deduct lim k S k = S = 0 \lim_{k\to\infty} S_k = \mathcal{S} = 0

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...